2013
DOI: 10.1016/j.nut.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nutritional status and the Glasgow Prognostic Score in patients with colorectal cancer

Abstract: Malnutrition is highly prevalent in patients with colorectal cancer. The nutritional status was associated with the GPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 22 publications
1
22
0
7
Order By: Relevance
“…Excess weight, visceral fat and abdominal obesity appears to be more disturbing than subcutaneous fat, and any further increase in BMI confers increased risk of developing colorectal cancer 19 , which, however, has not been confirmed in other studies with this tool 8,15 . Some authors also use weight loss as a nutritional screening marker.…”
Section: Anthropometric Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Excess weight, visceral fat and abdominal obesity appears to be more disturbing than subcutaneous fat, and any further increase in BMI confers increased risk of developing colorectal cancer 19 , which, however, has not been confirmed in other studies with this tool 8,15 . Some authors also use weight loss as a nutritional screening marker.…”
Section: Anthropometric Methodsmentioning
confidence: 84%
“…These results were also supported by our series of patients with esophageal, stomach and pan-creas tumors 8 . Moreover, in patients with esophageal or stomach cancer, SGA appears to be associated with the Glasgow Prognostic score (GPS) 19 . A study comparing PG-SGA with the Mini Nutritional Assessment (MNA) revealed that these tools seem appropriate to define elderly patients as malnourished 10 .…”
Section: Subjective Methodsmentioning
confidence: 99%
“…Recently, studies have demonstrated an important association between nutritional depletion and inflammation in cancer patients [4][5][6]14,16,17,[19][20][21][22] , including GIT tumors. Since cancer patients are in a constant state of inflammation, and considering the role of this systemic inflammation in progressive weight loss and muscle mass, cancer cachexia can be identified by the presence and alteration of certain inflammatory markers [5][6][7] .…”
Section: Resultsmentioning
confidence: 99%
“…En la actualidad, además de su componente de valoración del estado nutritivo, el IO se considera uno de los marcadores de la respuesta inflamatoria sistémica del paciente frente al tumor, ya que en dicha respuesta intervienen tanto la albúmina 9 como los linfocitos 10 . Por otra parte, también se ha descrito una correlación entre estado nutricional y respuesta inflamatoria en el carcinoma de colon 27 . Tanto la albuminemia como los linfocitos circulantes han sido analizados en trabajos previos como factores pronósti-cos de la evolución del cáncer colorrectal, bien de forma aislada 10,28 o en combinación con otras variables como el antígeno carcino-embrionario 8 y la proteína C reactiva (Indice de Glasgow) 5 .…”
Section: Discussionunclassified